2017
DOI: 10.1590/0074-02760160530
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type distribution and HPV16 intratype diversity in southern Brazil in women with and without cervical lesions

Abstract: BACKGROUND Increasing evidence suggests that human papillomavirus (HPV) intratype variants (specific lineages and sublineages) are associated with pathogenesis and progression from HPV infection to persistence and the development of cervical cancer.OBJECTIVES This study aimed to verify the prevalence of HPV infection and distribution of HPV types and HPV16 variants in southern Brazil in women with normal cytology or intraepithelial lesions.METHODS HPV typing was determined by L1 gene sequencing. To identify HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
3
0
8
Order By: Relevance
“…Another study conducted in a different region in Brazil also found a high prevalence of the lineage A of HPV16 in samples of high-and low-grade lesions, including cervical cancer. 29 In contrast, the D lineage of HPV16 showed a significant association with cervical cancer, compared with high-grade lesions, suggesting that the lineage D of HPV16 is involved in the progression of HPV16 infection to cervical cancer. Although this is a cross-sectional study, the present study provides novel data on the association between specific lineages of HPV16 and cervical cancer.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Another study conducted in a different region in Brazil also found a high prevalence of the lineage A of HPV16 in samples of high-and low-grade lesions, including cervical cancer. 29 In contrast, the D lineage of HPV16 showed a significant association with cervical cancer, compared with high-grade lesions, suggesting that the lineage D of HPV16 is involved in the progression of HPV16 infection to cervical cancer. Although this is a cross-sectional study, the present study provides novel data on the association between specific lineages of HPV16 and cervical cancer.…”
Section: Discussionmentioning
confidence: 86%
“…Another study conducted in a different region in Brazil also found a high prevalence of the lineage A of HPV16 in samples of high- and low-grade lesions, including cervical cancer. 29…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the A lineage of HPV 16 was the most frequent and although there was a trend of association with high-grade lesions (CIN2/CIN3), it was not possible to demonstrate a difference between these high-grade lesions and cervical cancer. A study carried out in another region of Brazil also found a high prevalence of the A lineage of HPV16 in samples of high-and low-grade lesions, including cancer [30].…”
Section: Discussionmentioning
confidence: 88%
“…Cada una de las teorías propuestas para esclarecer el efecto biológico de las coinfecciones por VPH en las células cervicales, se sustenta en evidencias de estudios poblacionales. Sin embargo, no existen investigaciones básicas que demuestren, desde el punto vista molecular y celular, las hipótesis propuestas por un sinnúmero de investigadores (196,197,200,201). Obviamente, esto se debe a las limitaciones para realizar estudios in vitro, por la incapacidad del VPH para replicarse en cultivos celulares, aunque se están desarrollando investigaciones para lograr este objetivo (202).…”
Section: Genotiposunclassified